In pursuit of Mr. Right: Constructed masculinities in Malay teen magazine - Shaik Ismail, Sharifah Fazliyaton (Elsevier Ltd., 2014)
This paper seeks to explore the representation of masculinities in the print media, notably Malay teenage magazine in Malaysia.Through an analysis of a regular column of twelve sequential issues of a bi-monthly magazine, Remaja, this paper examines how masculinities are constructed in this magazine.The analysis revealed that the magazine reinforces hegemonic masculine ideals, in particular, through romantic heterosexual relationships.The male's voice is dominant in shaping the behaviours of the females while the females are found to be overtly active in ensuring the progression of the romantic relationship.